Analyzing the Factors Affecting Adolescents' Ability to Provide First Aid for Burns at SMP Muhammadiyah 8 Surakarta - Irma Mustika sari; Erika Dewi Noorratri; Rini Widarti; Hesty Winda Hapsari; Dwi Sri Wahyuningsih (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Burns are among the most common types of injuries that occur in daily life, whether at home, school, or in the surrounding environment. The mortality and morbidity rates due to burns in developing countries are estimated to be approximately 11.6 per 100,000 population. These injuries most frequently occur at home, school, or the workplace, with children and adolescents being the most vulnerable groups to burn injuries resulting from daily activities. Objective: This study aims to analyze the factors that most significantly influence adolescents’ ability to provide first aid for burns at Muhammadiyah 8 Junior High School Surakarta. Method: The research design employed was logistic regression. A total of 100 respondents were selected using a purposive sampling technique, and the data were analyzed using logistic regression tests. Results: The majority of respondents were aged 11–14 years (46%), with 54% having a junior high school education. A total of 70 respondents (70%) obtained information from social media or the internet, 44 respondents (47%) had good knowledge, and 73 respondents (73%) had previously experienced burn injuries. In addition, 42 respondents (42%) administered first aid using running water, and 66 respondents (66%) were capable of providing burn first aid. The logistic regression test results showed that the source of information produced a p-value of 0.035 with an OR of 1.929 and a 95% CI of 1.048–3.551, indicating that the source of information was the most influential factor on the ability to perform burn first aid. Conclusion: Adolescents’ ability to perform burn first aid is influenced by several factors, including age, educational level, sources of information, knowledge level, history of burn injuries, and frequency of first aid practices. Among these, the source of information was identified as the most important factor enhancing adolescents’ ability to provide burn first aid. Adolescents with access to reliable sources of information, such as materials developed by healthcare professionals, school modules, or formal education, are more likely to acquire the ability to administer burn first aid earlier compared to those without such access.